2008
DOI: 10.1093/carcin/bgm259
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor regulates CD168 expression and signaling in prostate cancer

Abstract: Dysregulation of the androgen receptor (AR) and its signaling in the prostate often occurs during normal aging or after androgen ablation, consequently leading to the development of hormone-refractory prostate cancer (HRPC). Hyaluronan (HA) plays an important role in this transformation of androgen-independent cancer. Previous studies have shown that activation of the receptor for hyaluronan-mediated motility, CD168, was correlated with the Gleason's score, cancer stage, transformation and metastasis in >90% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 28 publications
4
31
0
1
Order By: Relevance
“…The present study was designed to investigate RHAMM expression in HCC and its clinical significance. The present study revealed that RHAMM mRNA expression was significantly upregulated (65.78%, 123/187) in 187 pairs of primary HCC tissues compared with their paired ANLTs; this result indicates that upregulation of RHAMM is a common incident in HCC, which is in accordance with the a previous study that demonstrated that RHAMM is upregulated in prostate cancer; furthermore, RHAMM proteins responding to HA stimulation led to activation of CD168/ROCK-signaling pathway, and the activation of HA-mediated CD168 signaling were associated with the cancer stage, Gleason's score, androgen-independent cell transformation and metastatic status of high-grade prostate cancer (14). Notably, p53 has been proposed to be able to repress expression of the RHAMM cell-surface and nuclear matrix protein (22), thus the expression of RHAMM, HA-mediated RHAMM signaling transduction and metastasis may be repressed by p53.…”
Section: Rhamm Mrna Clinical ----------------------------------------supporting
confidence: 92%
See 1 more Smart Citation
“…The present study was designed to investigate RHAMM expression in HCC and its clinical significance. The present study revealed that RHAMM mRNA expression was significantly upregulated (65.78%, 123/187) in 187 pairs of primary HCC tissues compared with their paired ANLTs; this result indicates that upregulation of RHAMM is a common incident in HCC, which is in accordance with the a previous study that demonstrated that RHAMM is upregulated in prostate cancer; furthermore, RHAMM proteins responding to HA stimulation led to activation of CD168/ROCK-signaling pathway, and the activation of HA-mediated CD168 signaling were associated with the cancer stage, Gleason's score, androgen-independent cell transformation and metastatic status of high-grade prostate cancer (14). Notably, p53 has been proposed to be able to repress expression of the RHAMM cell-surface and nuclear matrix protein (22), thus the expression of RHAMM, HA-mediated RHAMM signaling transduction and metastasis may be repressed by p53.…”
Section: Rhamm Mrna Clinical ----------------------------------------supporting
confidence: 92%
“…RHAMM is not only a modulator of growth factor receptor, but also has major roles in progression and proliferation of various types of cancer (9,11). RHAMM has been found in a variety of mammalian cells, including smooth muscle cells, endothelial cells, nerve cells, macrophages, spermatozoa (12,13), and certain types of tumor cell, including prostate (14), breast (15) and gastric (16) cancer, and B-cell chronic lymphocytic leukemia (17). However, whether the upregulation of RHAMM contributes to hepatocarcinogenesis of HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…26,32,[37][38][39][40] Different moleculare HA sizes (polysacharide lengths) have different biological functions. 24 Hyaluronidase degrades HA into angiogenic fragments 32 and HA directly stimulates tumor cell proliferation, epithelial to mesenchymal transition, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of androgen and AR is essential for regulating HA-mediated cancer progression via the CD168 / ROCK signal transduction pathway and the androgen receptor dysregulation not only causes CD168 over expression but also activates HA-mediated CD168 signaling in malignant cancer progression and metastasis of hormone refractory prostate cancer. [7,8] In our case, on retrospect, the tumor in core biopsy sample did not express CD168 whereas expression was seen in some metastatic cells in testis. It can be argued that the absence of CD168 in the core biopsy sample of carcinoma may be a sampling error as the core sample comprised of adenocarcinoma of Gleason's score 7 whereas the metastatic adenocarcinoma had a higher degree of anaplasia.…”
Section: Discussionmentioning
confidence: 46%
“…[6] CD 168 or Rhamm is a receptor for hyaluronan mediated motility and has been recently implicated in the evolution of androgen independent prostate cancer and metastasis in human bone marrow endothelium. [7,8] We report an unusual case of testicular metastasis of a prostatic adenocarcinoma with prominent seminoma like nucleoli, intertubular infiltrative pattern and focal expression of CD168.…”
Section: Introductionmentioning
confidence: 97%